On a Certain Lithuanian Purpose Clause Construction - Holvoet, Axel (Lietuvių kalba, 2024)
The article deals with the use of the Lithuanian anteriority converb in -us in a certain type of purpose clauses whose implicit subject is coreferential with the (often also implicit) main clause subject or agent (as in kad veltui neišmetus pinigų ‘in order not to throw money away’). The article offers a historical account for its rise based on internal reconstruction. It is argued that the anteriority converb was introduced as a pseudo-conditional strategy used to avoid a factive reading in constructions with evaluative predicates (as in gerai būtų suradus... = gerai būtų, jeigu surastume... ‘it would be a good thing if we found…’). From evaluative constructions the converb then spread to optative clauses with kad tik ‘if only’ (gerai būtų suradus ‘it would be a good thing to find…’ → kad tik suradus... ‘if only one could find…’). Apart from a semantic shift (from evaluative to desiderative/deontic) this also involved a process of syntactic insubordination. In a subsequent process of resubordination, constructions with the anteriority converb finally came to function as adverbial purpose clauses. In the final part of the article it is argued that the negative view prescriptivist sources take of purpose clauses with the anteriority converb might be up for a revision.